Early intervention in scar management and cutaneous burns with autologous platelet‐rich plasma. (22nd April 2018) - Ruiz, Aura; Cuestas, Daniel; Garcıa, Paula; Quintero, Jose; Forero, Yency; Galvis, Ingrid; Velasquez, Oscar
Summary: Burn management options are controversial and a multiple‐handled issue. However, platelet‐rich plasma is gaining interest in several medical fields. Dermatologist worldwide are already publishing some reports about its benefits and personal experiences in their practices. A 40‐year‐old female with a second‐degree burn by VASER‐type liposculpture was treated with platelet‐rich plasma and followed up for 10 months. After treatment, she showed rapid improvement with an adequate cicatrization results. Some studies suggest that the use of platelet‐rich plasma which contains cytokines and growth factors that participate in cellular repair and cellular differentiation, thus improving healing time and re‐epithelization. We present the case of a patient with a second‐degree burn that rapidly improved with autologous platelet‐rich plasma.